2012
DOI: 10.1590/s1676-26492012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in cerebrospinal fluid of children with West syndrome

Abstract: In this study we aimed to determine the levels of tumor necrosis factor beta (TNF-b), interleukin (IL) 1-beta (IL-1b), IL-5, IL-10, and interferon gamma (IFN-g ) in CSF from children during the onset of West syndrome (WS). We observed elevated levels of IL-1b and IFN-g correlated to clinical, EEG, therapeutic response, and follow-up suggesting the involvement of immune response in WS. These results suggest that inflammatory and immunologic mediators may play a role in the pathophysiologic mechanisms of infanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, no statistically significant difference was observed between IL-2 levels. Sousa et al showed an increase in IL-1b and IFN-g levels by investigating IL-1b, IL-5, IL-10, TNF-b and IFN-g levels in CSF specimens from four patients with infantile spasm, three symptomatic and one from the cryptogenic group, aged 4-12 months [15]. Liu et al reported significantly higher IL-2 and TNF-alpha levels in patients with West syndrome compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, no statistically significant difference was observed between IL-2 levels. Sousa et al showed an increase in IL-1b and IFN-g levels by investigating IL-1b, IL-5, IL-10, TNF-b and IFN-g levels in CSF specimens from four patients with infantile spasm, three symptomatic and one from the cryptogenic group, aged 4-12 months [15]. Liu et al reported significantly higher IL-2 and TNF-alpha levels in patients with West syndrome compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%